The Role of Advisors in Improving the Teaching Quality of Sunday School Teachers - Wiliem Yacob Hetharion (International Journal of Education, Information Technology, and Others, 2021)
This study aims to determine the role of caregivers in improving the teaching quality of caregivers. The research method used in this study is a qualitative method using a descriptive qualitative approach. The results of the study can be described as follows, 1) The role of caregivers in improving the quality of teaching in Klasis North Ambon Island GPM Housetiga Sector Pisga Congregation, namely the role of extension workers, skill actors, creative experience designers, creativity drivers, learning resources, motivators, change agents and communicators . The role that has not been carried out optimally by the caregiver supervisor in the GPM Rumahtiga Sector Pisga Congregation is as an evaluator. 2) The role of caregivers as counselors, actors of skills, designers of creative experiences, drivers of creativity, learning resources, motivators, agents of change and communicators can improve the quality of teaching